Integrating Digital Media in Early Language Learning for Young Children with Special Needs: A Study on Learners Aged 4-5 years - Siti Suqhiroh; Sri Katoningsih (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2025)
The utilization of digital media in language learning for children with special needs aged 4-5 years at KB Aisyiyah Pracimantoro. The research objective is to determine how digital media can enhance the language abilities of children with special needs and to identify the challenges educators face in its implementation. The research method uses a qualitative approach with a case study design. Data were collected through in-depth interviews with the Principal, educators, and parents, as well as 30 minutes of participatory observation in class using a structured observation guide that assessed seven ability indicators of children on a scale of 1-4. Data analysis techniques used the Miles and Huberman interactive model, which includes data reduction, data presentation, interpretation, and conclusion. Data validity was ensured through source triangulation and method triangulation. The research results show that digital media, particularly educational videos with songs and movements, as well as interactive educational applications, are effective in improving the language abilities of children with special needs by increasing focus, motivation, vocabulary acquisition, and articulation. Interview results confirm that children who previously had difficulty pronouncing simple words showed significant development after routinely using digital media. However, implementation faces challenges, including limited devices and internet connections, difficulty finding specific content, managing children’s behavior, and the need for continuous teacher training. The research concludes that digital media is a potential tool for language learning among children with special needs, but requires infrastructure support, relevant content development, and increased educator capacity for optimal use.